ATP‐binding cassette subfamily B member 1 1236C/T polymorphism significantly affects the therapeutic outcome of tacrolimus in patients with refractory ulcerative colitis. Issue 9 (September 2017) - Onodera, Motoyuki; Endo, Katsuya; Kakuta, Yoichi; Kuroha, Masatake; Kimura, Tomoya; Hiramoto, Keiichiro; Kanazawa, Yoshitake; Negoro, Kenichi; Shiga, Hisashi; Kinouchi, Yoshitaka; Shimosegawa, Tooru
Abstract: Background and Aim: Tacrolimus is now considered to be one of the main therapeutic options for refractory ulcerative colitis. Both cytochrome P‐450 3A5 (CYP3A5) and ATP‐binding cassette subfamily B member 1 (ABCB1) associated with tacrolimus metabolism are known to have several genetic polymorphisms. However, it remains controversial whether these polymorphisms affect the therapeutic efficacy for ulcerative colitis. We aimed to investigate the influence of both CYP3A5 and ABCB1 polymorphisms on the efficacy of tacrolimus in ulcerative colitis treatment under the tight dose‐adjusting strategy. Methods: Sixty‐one Japanese patients with ulcerative colitis treated with tacrolimus were enrolled retrospectively. Tacrolimus treatment was performed using the tight dose‐adjusting strategy. Genotyping for CYP3A5 *3, ABCB1 1236C>T, 2677G>A, T, and 3435C>T were performed, and the clinical outcomes at 12 weeks after the initiation of tacrolimus were compared among the genotypes. Results: There was no association between the CYP3A5 genotypes and therapeutic efficacy. In contrast, a significant association was observed with the ABCB1 1236C > T polymorphism and therapeutic efficacy. The ABCB1 1236CC+CT groups ( n  = 41) had a significantly higher response rate (73% vs 35%; P  = 0.004) and remission rate (61% vs 20%; P  = 0.002) than the TT group ( n  = 20). The multivariate logistic regression analysis also revealed that ABCB1 1236C>T was identified as an independent factor associated with remission. Conclusions: ABCB1 1236C>T polymorphism significantly affects the therapeutic efficacy of tarcolimus at 12 weeks under the tight dose‐adjusting treatment for ulcerative colitis.